Parents, "they're driving me crazy!" - Havelin, Kate, 1961- (Mankato, Minn. : LifeMatters, 2000)
Describes typical relationships between teenagers and their parents, reasons for conflicts, and strategies for improving relationships
Includes bibliographical references and index
Keywords: Parent and child -- Juvenile literature; Parents -- Juvenile literature; Parent and child